2016
DOI: 10.1590/s0100-83582016340100004
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Yield Loss in a Two Species Competition with Emex australis and Emex spinosa

Abstract: -Emex australis and E. spinosa are significant weed species in wheat and other crops. Information on the extent of competition of the Emex species will be helpful to access yield losses in wheat. Field experiments were conducted to quantify the interference of tested weed densities each as single or mixture of both at 1:1 on their growth and yield, wheat yield components and wheat grain yield losses in two consecutive years. Dry weight of both weed species increased from 3-6 g m -2 with every additional plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 12 publications
(16 reference statements)
2
7
0
Order By: Relevance
“…Our findings are parallel with the results ofMorales-Payan (2000), who stated 63% reduction in tomatoes yield with increasing 0-12 parthenium plants m -2 Bridges et al (1992). also reported 4 to 54% reduction in peanut yield as density of Euphorbia heterophylla increased from 1-32 plants in 5 m long row Javaid et al (2016). who affirmed that weeds competed with wheat and significantly decreased yield.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…Our findings are parallel with the results ofMorales-Payan (2000), who stated 63% reduction in tomatoes yield with increasing 0-12 parthenium plants m -2 Bridges et al (1992). also reported 4 to 54% reduction in peanut yield as density of Euphorbia heterophylla increased from 1-32 plants in 5 m long row Javaid et al (2016). who affirmed that weeds competed with wheat and significantly decreased yield.…”
supporting
confidence: 91%
“…Saeed et al (2012) also reported sever yield reduction in maize by increasing weed density. Similarly, Javaid et al (2016) reported that E. spinosa and E. australis significantly decreased biological yield of yield. Armin and Asghripour (2011) described that wild oat at high density decreased grain yield of wheat by decreasing number of spike bearing tiller per plant and number of spike per unit area.…”
Section: -Grain Weight (G)mentioning
confidence: 83%
See 2 more Smart Citations
“…Being a botanical pest, weeds share similar trophic level as that of crop plants, and weed-crop competition results in a substantial crop yield loss (Ali et al, 2015b;Javaid et al, 2016;Ramesh et al, 2017). The cost incurred in M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 99%